Book influencers in the library? - Szabó, Dóra; Dani, Erzsébet (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
The digital revolution has transformed reading promotion in a world where technology competes with traditional entertainment, posing challenges for libraries, especially in engaging audiences. Adapting actively is crucial to making reading appealing. The rise of book influencers and reading promoters on social media is pivotal for reading education, offering libraries opportunities to diversify programs. Using the "walkthrough" method on four platforms, our research identified 60 Hungarian book influencers and reading promoters. Structured interviews with 23 influencers aimed to unveil their activities, motivations, and the aspirations and reading experiences behind their content. The study contributes to literary and cultural mediation, exploring the intersection between libraries and literacy promoters. It addresses how literacy promoters can enhance reading promotion in the community, emphasizing their role in generating interest in books and literature. Findings suggest that social media and influencers complement libraries' literacy strategies, benefiting both libraries and readers. Collaborating with influencers can foster a reading culture aligned with the digital era's demands. Encouraging influencers to collaborate could also educate their followers, transforming them into library users.